Brilliance as Cognitive Complexity in Aboriginal Australia. Issue 2 (26th July 2017) - Turpin, Myfany; Fabb, Nigel
Abstract : Writers on Australian Aboriginal ceremonial practices and contemporary commercial art have identified properties that can be described as producing 'brilliance', the term used by Howard Morphy (1989) for Yolngu visual art. Brilliance involves the emotionally charged knowledge that Ancestral power is manifest. We suggest that, in Australian Aboriginal ceremonial practices and art, two kinds of brilliance are at work, both of which we exemplify using evidence from songs and languages of the Arandic and Warlpiri region of Central Australia. One kind of brilliance is manifest as visual brightness and whiteness, the other relates to a variety of cognitive complexities that involve diverse combinations of parts both within and across modalities of expression. In extending the notion of brilliance from the visuality of brightness to include cognitive complexity, we follow other work on Australian Aboriginal ceremonial practices. Seeking to understand why these properties should produce particular emotional and epistemic effects in participants, we draw on psychological accounts of the sublime and awe (Keltner and Haidt 2003; Miall and Kuiken 1994), which we treat as part of the same broad family of experiences as the experience of brilliance. We suggest both visual brightness and cognitive complexity represent an 'extremity' that as such places considerable cognitive demands on the participants. These extraordinary cognitive demands stimulate emotion and produce the experience of Ancestral power and surprising moments of insight.